Pemberdayaan Kader Dalam Deteksi Dini Penyakit Tidak Menular di Desa Dopang Kecamatan Gunung Sari Lombok Barat [Empowering Cadres in Early Detection of Non-Communicable Diseases in Dopang Village, Gunung Sari Subdistrict, West Lombok] - Mardiatun, Mardiatun; Wijayanti, Sri Puja Warnis; Mawaddah, Ely; Sentana, Aan Dwi; Hadi, Irwan (UKInstitute, 2026)
Abstract. Non-communicable diseases (NCDs) are a global health problem with high morbidity and mortality rates, especially in developing countries. One of the government’s efforts to reduce NCD rates is through the establishment of Integrated Counseling Posts (Posbindu) for NCDs, which involve health cadres in the early detection of risk factors. However, cadres' skills in anthropometric and blood pressure examinations remain limited due to a lack of training. This community service activity aims to improve the knowledge and skills of cadres in early detection of NCDs in Dopang Village, Gunung Sari Subdistrict, West Lombok. The implementation methods included lectures, discussions, and demonstrations of anthropometric examinations (body weight, height, body mass index, waist circumference) and blood pressure measurements using a booklet as a media tool. The activity involved 30 health cadres from 11 villages, with 2-3 cadres representing each village. The results showed that before the training, most cadres had never received assistance related to early detection of NCDs. After counseling and demonstrations, all cadres were able to perform blood pressure and anthropometric examinations according to SOPs, calculate BMI, and record examination results on forms. Cadres’ skills improved along with high enthusiasm and direct assistance from the service team. In conclusion, education and demonstration-based training effectively increased cadres’ capacity in early detection of NCDs, thereby strengthening prevention and control efforts at the community level. Abstrak. Penyakit Tidak Menular (PTM) merupakan masalah kesehatan global dengan angka morbiditas dan mortalitas yang tinggi, khususnya di negara berkembang. Salah satu upaya pemerintah untuk menekan angka PTM adalah melalui pembentukan Pos Pembinaan Terpadu (Posbindu) PTM yang melibatkan kader kesehatan dalam deteksi dini faktor risiko. Namun, keterampilan kader dalam pemeriksaan antropometri dan tekanan darah masih terbatas akibat minimnya pelatihan. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan kader dalam deteksi dini PTM di Desa Dopang, Kecamatan Gunung Sari, Lombok Barat. Metode pelaksanaan meliputi ceramah, diskusi, dan demonstrasi pemeriksaan antropometri (berat badan, tinggi badan, indeks massa tubuh, lingkar perut) serta pengukuran tekanan darah dengan menggunakan media booklet. Peserta kegiatan berjumlah 30 kader kesehatan dari 11 desa dengan perwakilan 2-3 kader. Hasil kegiatan menunjukkan bahwa sebelum pelatihan sebagian besar kader belum pernah mendapatkan pendampingan terkait deteksi dini PTM. Setelah dilakukan penyuluhan dan demonstrasi, seluruh kader mampu melakukan pemeriksaan tekanan darah dan antropometri sesuai SOP, menghitung IMT, serta mencatat hasil pemeriksaan pada formulir. Keterampilan kader meningkat seiring dengan tingginya antusiasme dan pendampingan langsung oleh tim pengabdian. Kesimpulannya, pelatihan berbasis edukasi dan demonstrasi efektif meningkatkan kapasitas kader dalam deteksi dini PTM, sehingga dapat memperkuat upaya pencegahan dan pengendalian PTM di tingkat komunitas.